PEMANFAATAN MEDIA SOSIAL INSTAGRAM SEBAGAI MEDIA INFORMASI DAN KOMUNIKASI POLRESTA SURAKARTA KEPADA MASYARAKAT - Saputro, Alfiano Imam; Suryo, Herning (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
ABSTRACT Technological developments in the field of communication and information have given rise to media designed for the purpose of sharing information and communication with followers. The media is called Instagram, on Instagram its users are given the freedom to upload anything that comes from its users. The existence of Instagram also makes it easier for organizations, agencies or companies to carry out communication processes in order to maintain good correlation with society. The Surakarta Police is one of the agencies that uses Instagram social media in the process of conveying information and communicating with the public. The aim of this research is to describe the use of Instagram social media as an information and communication medium at the Surakarta Police. And in this research, researchers used new media theory, where Instagram is included in this category. Where utilization also includes features on Instagram. The method used in this research uses a qualitative descriptive method. Data obtained through interviews with one of the public relations members of the Surakarta Police and the Community. Apart from that, data is also obtained through observation and documentation. The results of this research are that the use of Instagram social media as an information and communication medium at the Surakarta Police is informative, quite effective and gets a good response. And from these results it can be concluded that the use of Instagram social media can help the public to continue to update information on what is happening in the Surakarta area. Keywords: new media, Instagram, Surakarta Police